Pengaruh Media Gambar Terhadap Penguasaan Mufrodat Siswa MTs Islamiyah Banat Senori Tuban - Habib Abdul Halim (LUGHATI: Jurnal Pendidikan Bahasa Arab, 2024)
Image media is one of the Arabic language teaching methods that is used to convey and facilitate Arabic language subjects, and because vocabulary is one of the elements of the language, and this is where Arabic is. Therefore, understanding vocabulary is very important in teaching foreign languages, meaning Arabic. In this scientific research entitled